Linear magnetoelastic coupling and magnetic phase diagrams of the buckled-kagomé antiferromagnet Cu3Bi(SeO3)2O2Cl - Spachmann, Sven; Berdonosov, P.; Markina, M.; Vasiliev, A.; Klingeler, Rüdiger (Scientific reports, 2022)
Single crystals of Cu$$_3$$Bi(SeO$$_3$$)$$_2$$O$$_2$$Cl were investigated using high-resolution capacitance dilatometry in magnetic fields up to 15 T. Pronounced magnetoelastic coupling is found upon evolution of long-range antiferromagnetic order at $$T_{N}$$ $$= 26.4(3)$$ K. Grüneisen analysis reveals moderate effects of uniaxial pressure on $$T_{N}$$, of 1.8(4) K/GPa, $$-0.62(15)$$ K/GPa and 0.33(10) K/GPa for